Evolution of methods and forms of digital transformation of business processes in enterprises - V. V. Mukhin (Вестник Северо-Кавказского федерального университета, 2024)
Introduction. New digital technologies and the pace of their growth and implementation in the economy entail changes in management processes. The object of the study is digital transformation of managerial impact on business processes in organizations and enterprises at the present stage of development of economic relations. Goal. The purpose of the study is to identify new methods and forms of digital transformation of business processes in a new strategy for the development of economic activities of enterprises and organizations. Materials and methods. Within the framework  of  a  systems  approach,  using  the  historical  method,  comparative  analysis  and  synthesis,  the  economic  specifics  of  the  digital  transformation of business processes in Russian enterprises are revealed, and with the help of formal logic, the methods and forms of digital transformation of business processes are clarified. Results and discussion. The article analyzes the evolution of the cause-and-effect relationship of the development of digital transformation on management business processes in enterprises and organizations. The logic and hierarchy of applying methods and forms of digital transformation of business processes have been clarified. In the process of analyzing and clarifying the characteristics of digital processes and phenomena, the author’s understanding of the category of digital transformation of business processes was formulated. Conclusion. At the theoretical level, the tools, forms and methods used in the process of digital transformation of business processes of an enterprise or organization are grouped and their characteristics and functional purposes are clarified. In practical terms it will serve as a real basis for developing the management competencies of the management of enterprises and organizations in order to optimize routine processes for communications and the sale of goods and services.